Altered Gut Microbiota in Children With Hyperuricemia - Yuan, Xin; Chen, Ruimin; Zhang, Ying; Lin, Xiangquan; Yang, Xiaohong (Frontiers in Endocrinology, 2022)
Background In adults, gut dysbiosis may contribute in the pathogenesis of gout. However, the characteristics of gut microbiota in children with hyperuricemia (HUA) in the absence of clinical gout has not been explored. Objective This present study was performed to explore the changes in gut microbiome in children with HUA and discern correlations between the gut microbiota and HUA. Methods A total of 80 children were enrolled in this study, they were divided to HUA and controls (Con) according to the level of serum uric acid (UA). The composition of gut microbiota was investigated by 16S rRNA-based metagenomics. Results PCoA analysis revealed that the gut microbiota samples from the HUA group were clustered together and separated partly from the Con group. There was no difference of alpha-diversity between two groups. However, Spearman’s correlation analysis revealed that serum UA level positively correlated with genus Actinomyces, Morganella, and Streptococcus, and negatively associated with the producers of short-chain fatty acids (SCFAs), such as Alistipes, Faecalibacterium, Oscillospira, and the sulfidogenic bacteria Bilophila. The Con subjects had members of the genus Alistipes and Bilophila that were significantly more prevalent than the HUA subjects. Compared to Con cohort, metabolic pathway predictions found that the superpathways of purine nucleotides de novo biosynthesis were decreased in HUA subjects, whereas the superpathway of purine deoxyribonucleosides degradation was increased. Conclusion The structure of the gut microbiota in children with HUA differs from Con. Although causality cannot be established, modification in the microbiota in that SCFA and sulfide production effects purine metabolism may promote HUA.